Tailoring magnetic properties of multicomponent layered structure via current annealing in FePd thin films. Issue 1 (December 2017) - Cialone, Matteo; Celegato, Federica; Coïsson, Marco; Barrera, Gabriele; Fiore, Gianluca; Shvab, Ruslan; Klement, Uta; Rizzi, Paola; Tiberto, Paola
Abstract Multicomponent layered systems with tailored magnetic properties were fabricated via current annealing from homogeneous Fe67 Pd33 thin films, deposited via radio frequency sputtering on Si/SiO2 substrates from composite target. To promote spontaneous nano-structuring and phase separation, selected samples were subjected to current annealing in vacuum, with a controlled oxygen pressure, using various current densities for a fixed time and, as a consequence, different phases and microstructures were obtained. In particular, the formation of magnetite in different amount was observed beside other iron oxides and metallic phases. Microstructures and magnetic properties evolution as a function of annealing current were studied and interpreted with different techniques. Moreover, the temperature profile across the film thickness was modelled and its role in the selective oxidation of iron was analysed. Results show that is possible to topologically control the phases formation across the film thickness and simultaneously tailor the magnetic properties of the system.